Deconstructing language learners’ feelings of inferiority through teletandem - Zulaica-Gómez, Paula A. (Revista do GEL, 2018)
Teletandem is based on principles of reciprocity, equality, collaboration, and autonomy between two participants who are eager to learn their target language and share their knowledge of the one in which they are proficient at the same time. While this is true, each party comes to the experience with their own context, perception, and attitudes towards their target language, and thus, their circumstances are unequal, particularly those pertaining to their motivation for enrolling in a foreign language class. In the case of Mexican learners of English as a foreign language, several sociocultural factors, resulting from the country’s colonial history affect their motivation and attitude towards English. This article focuses on a) how perceptions and attitudes towards English affect the willingness of Mexican learners to participate in teletandem sessions by self-imposing a lower station within a preconceived social hierarchy, and b) how teletandem can break through these preconceived notions and change the way they perceive themselves and their partners. Results of post-session evaluations reveal how after participating in teletandem and reflecting on the experience, they report increased motivation and confidence in their target language skills.